The use of computer navigation in reverse shoulder arthroplasty revision: a case report - Tarallo, Luigi; Micheloni, Gian Mario; Giorgini, Andrea; Donà, Alessandro; Porcellini, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Revision shoulder surgery is always a challenge, especially in the management of periprosthetic joint infection. Staged surgery with antibiotic-loaded cement spacer, seems to yield satisfactory and encouraging results. New technologies such as computer navigation are additional tools that could aid surgeons in particular conditions where the native anatomy is distorted. This study presents the unique experience of revision shoulder surgery with computer navigation assistance. Benefits related to this approach could lead to better prosthesis longevity and survivorship.